Formulasi Jagurah Tepung Ubi Jalar Kuning, Tepung Jagung Kuning, dan Tepung Beras Merah sebagai Snack bagi Penderita Diabetes Melitus - Andrafikar Andrafikar; Ummi Mahmudah; Mamat Rahmat; Mulus Gumilar (Poltekkes Kemenkes Padang, 2024)
The prevalence of diabetes mellitus (DM) in Indonesia is predicted to increase from 10.7 million in 2019 to 13.7 million by 2030. If not properly managed, DM can lead to various complications, making proper management essential. One such approach is to provide foods with a low glycemic index and high soluble fiber content. This study aims to examine the organoleptic properties and fiber content of modified baked sagun (Jagurah). The research design was an experiment using a completely randomized design (CRD) with three treatments, conducted in the Food Technology Laboratory, Department of Nutrition, Padang. Organoleptic testing involved 25 trained panelists using a 7-point scale, while proximate analysis was performed at the BSPJI Laboratory in Padang. Data analysis was conducted using the Mann-Whitney test for normal data and Kruskal-Wallis test for non-normal data. The results showed no significant differences in color, texture, aroma, and overall acceptability (p > 0.05), but there was a significant difference in taste (p = 0.00). The best formula was F3. The best Jagurah contains 327 kcal, 12.07 g protein, 11.5 g fat, 43.8 g carbohydrates, and 6.75 g fiber per 100 g. The price for a 60 g serving is Rp 4,000.